3-Bromopyruvate as an Alternative Option for the Treatment of Protothecosis - Jagielski, Tomasz; Niedźwiecka, Katarzyna; Roeske, Katarzyna; Dyląg, Mariusz (Frontiers in Pharmacology, 2018)
Protothecosis is an unusual infection of both humans and animals caused by opportunistically pathogenic microalgae of the genus Prototheca. Until now, no standardized treatment protocols exist for the protothecal disease, boosted by a remarkable resistance of Prototheca spp. to a wide array of antimicrobial agents currently available in clinical use. Consequently, there is an urgent need for new effective drugs against Prototheca algae. In this study, the anti-Prototheca activity of 3-bromopyruvate (3BP), either alone or in combination with amphotericin B (AMB) was assessed in vitro, as well as the cytotoxicity of 3BP towards the bovine mammary epithelial cells and murine skin fibroblasts. The mean minimum inhibitory concentrations (MIC) and minimum algaecidal concentrations (MAC) were 0.85±0.21 and 2.25±0.54 mM for Prototheca wickerhamii, 1.25±0.47 and 4.8±1.03 mM for Prototheca blaschkeae, and 1.55±0.69 and 5.6±1.3 mM for Prototheca zopfii gen. 2, respectively. For all Prototheca strains tested, a synergistic interaction between 3BP and AMB was observed, resulting in about 4-fold reduction of their individual MICs, when used together. The elevated content of intracellular glutathione (GSH) was associated with a decreased susceptibility to 3BP. Both epithelial and fibroblast cells retained high viability upon treatment with 3BP at concentrations equivalent to the highest MIC recorded (3 mM) and 10-fold higher (30 mM), with the mean cell viability exceeding 80%, essentially the same as for the untreated cells. The results from these in vitro studies emphasize the high activity of 3BP against the Prototheca algae, its synergistic effect when used in combination with AMB, and the safety of the drug towards the tested mammalian cells. Along with the advantageous physico-chemical and pharmacokinetic properties, 3BP may be considered an effective and safe novel agent against the protothecal disease.